2000
DOI: 10.1016/s0893-133x(00)00092-0
|View full text |Cite
|
Sign up to set email alerts
|

Somatodendritic 5-HT1A Autoreceptors Mediate the Anti-Aggressive Actions of 5-HT1A Receptor Agonists in Rats An Ethopharmacological Study with S-15535, Alnespirone, and WAY-100635

Abstract: Serotonin; Hypothermia; Rat A dysregulation of brain serotoninergic (5-HT) transmission, particularly at 5-HT 1A receptors, is implicated in the pathophysiology of anxiety, depression, and impulsive states like violent aggression (i.e., Coplan et al. 1995;Maes and Meltzer 1995;Berman et al. 1997). CorFrom the Department of Animal Physiology (SFB, JMK), University of Groningen, The Netherlands; and the Institut de Recherches Internationales Servier (ML, EM), Courbevoie Cedex, France.Address correspondence to:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 38 publications
2
56
0
1
Order By: Relevance
“…Both S-15535 and 8-OHDPAT were found to enhance cocaine's psychomotor effects in SERT +/+ and SERT −/− rats. While the effects of 0.25 mg/kg 8-OHDPAT are most likely to be mediated by postsynaptic receptors, as reported by others (Müller et al 2007), the effects of S-15535 may be more difficult to interpret because of its pharmacological profile (Millan et al 1993a;Newman-Tancredi et al 1999;de Boer et al 2000). In contrast to 8-OHDPAT, S-15535 by itself had no effect on activity, which suggests at least that S-15535 did not act as postsynaptic 5-HT 1A receptor agonist.…”
Section: Enhanced Rewarding Properties Of Cocaine In Sertmentioning
confidence: 72%
See 2 more Smart Citations
“…Both S-15535 and 8-OHDPAT were found to enhance cocaine's psychomotor effects in SERT +/+ and SERT −/− rats. While the effects of 0.25 mg/kg 8-OHDPAT are most likely to be mediated by postsynaptic receptors, as reported by others (Müller et al 2007), the effects of S-15535 may be more difficult to interpret because of its pharmacological profile (Millan et al 1993a;Newman-Tancredi et al 1999;de Boer et al 2000). In contrast to 8-OHDPAT, S-15535 by itself had no effect on activity, which suggests at least that S-15535 did not act as postsynaptic 5-HT 1A receptor agonist.…”
Section: Enhanced Rewarding Properties Of Cocaine In Sertmentioning
confidence: 72%
“…However, combined with our observation that 8-OHDPAT-induced activity and 5-HT syndrome, which are postsynaptically mediated (Yamada et al 1988), were reduced in SERT −/− rats relative to SERT +/+ rats in the locomotor tests, the 8-OHDPATinduced hypothermia findings imply that predominantly postsynaptic 5-HT 1A receptors are involved. This view is further supported by the lack of a hypothermic effect of S-15535 (Millan et al 1993a;de Boer et al 2000). Previous studies have convincingly demonstrated that this compound is a full somatodendritic 5-HT 1A receptor agonist and has only weak partial agonistic or even antagonistic properties at postsynaptic 5-HT 1A receptor (Millan et al 1993a;Newman-Tancredi et al 1999;de Boer et al 2000).…”
Section: Enhanced Rewarding Properties Of Cocaine In Sertmentioning
confidence: 82%
See 1 more Smart Citation
“…Both agonists reduce aggression in different experimental procedures but cause impairment of motor activity or stimulation (7,9,12). However, several recently developed 5-HT 1A receptor agonists like alnespirone and S-15535 have more specific anti-aggressive effects in male rats (16). The 5-HT 1B receptor agonists, such as CP-94,253, anpirtoline and zolmitriptan, have shown anti-aggressive effects in male mice when administered systemically (17).…”
mentioning
confidence: 99%
“…Therefore, it is possible for B. gauderio 5HT 1A R's transcription to be regulated by GCs. Thus GCs could exert negative feedback on 5HT 1A R expression by downregulating transcription, thereby suppressing aggression through action at 5HT 1A autoreceptors (de Boer et al, 2000), and reducing electric signal magnitude through action at 5HT 1A post-synaptic receptors . I currently do not know whether 5HT 1A R is found as an autoreceptor and postsynaptic receptor in the hypothalamus of B. gauderio.…”
Section: Discussionmentioning
confidence: 99%